2011
DOI: 10.1029/2011gl046875
|View full text |Cite
|
Sign up to set email alerts
|

The rarity of terrestrial gamma-ray flashes

Abstract: We report on the first search for Terrestrial Gamma‐ray Flashes (TGFs) from altitudes where they are thought to be produced. The Airborne Detector for Energetic Lightning Emissions (ADELE), an array of gamma‐ray detectors, was flown near the tops of Florida thunderstorms in August/September 2009. The plane passed within 10 km horizontal distance of 1213 lightning discharges and only once detected a TGF. If these discharges had produced TGFs of the same intensity as those seen from space, every one should have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
3
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 30 publications
5
61
3
1
Order By: Relevance
“…The frequency of glows that ADELE observed at cruise altitude-despite not passing directly through as on 21 August-demonstrates that the glow discharge process is not rare or anomalous, especially when compared with TGFs 40 . All of the other glows, except one, occurred when the Gulfstream V was passing near an active lightning cell.…”
Section: Discussionmentioning
confidence: 88%
“…The frequency of glows that ADELE observed at cruise altitude-despite not passing directly through as on 21 August-demonstrates that the glow discharge process is not rare or anomalous, especially when compared with TGFs 40 . All of the other glows, except one, occurred when the Gulfstream V was passing near an active lightning cell.…”
Section: Discussionmentioning
confidence: 88%
“…However, the flux of these gamma rays is generally many orders of magnitude lower than TGFs. Two events that did have TGF‐like fluxes were a ground‐based observation of a TGF‐like burst seen at sea level in Florida [ Dwyer et al , 2004a] and an observation of a TGF by the ADELE instrument onboard an NCAR‐NSF Gulfstream‐V aircraft [ Smith et al , 2011]. Both of these events appeared to be very similar to the TGFs observed from space.…”
Section: Introductionmentioning
confidence: 94%
“…Currently, most TGFs are believed to be produced inside thunderclouds during the initial stage of upward positive intracloud (IC) lightning [ Stanley et al , 2006; Lu et al , 2010; Shao et al , 2010; Connaughton et al , 2010; Lu et al , 2011]. However, how the lightning is related to the TGF production has not been clear, nor has it been well understood why some lightning produces TGFs while many others do not [ Splitt et al , 2010; Smith et al , 2011].…”
Section: Introductionmentioning
confidence: 99%
“…Is the TGF-generating process common and just the source altitude (Williams et al 2006; dictates whether the TGF is detectable at high altitudes? Recent work suggests not (Smith et al 2011b) but identifying a definitive signature of TGF-producing lightning flashes would give important insight into what is different about these flashes.…”
Section: The Tgf-lightning Connectionmentioning
confidence: 99%
“…The calculated luminosity of this event given the 10 km distance was comparable to that associated with TGFs seen from space (about 10 17 relativistic electrons needed). Perhaps more importantly, ADELE passed within 10 km of over 1000 other discharges detected by ground-based sferic networks without detecting any other TGF (Smith et al 2011b). The authors concluded that TGFs, even if there was a population too faint to be seen from orbit, are rare events, only associated with 0.1-1 % of lightning flashes.…”
Section: Adele Tgf Observationsmentioning
confidence: 99%